implementasi kurikulum terpadu dan konsep belajar tematik pada lembaga PAUD - Mahbubah, Aprilia Zinatul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to describe the implementation of the integrated curriculum (2013) and the concept of thematic learning in early childhood, as well as find out the appropriate implementation of learning for early childhood. By using qualitative methods on previous research related to the implementation of an integrated curriculum and the concept of thematic learning in early childhood which basically at that age is the age called the Golden Age where at this age the stimulation for development is very fast so that it requires the role of adults around him. Therefore it can be concluded that proper education in early childhood is very important for the five aspects of child development to shape the child's personal character in the future.